Marketing Strategy and the Role of Public Relations in the Fintech Lending User Acquisition Process: A Case Study of Bantusaku in Indonesia - Arnoldyth Rodes Medo; Kartika Singarimbun (Eduvest - Journal of Universal Studies, 2026)
The rapid growth of the financial technology (fintech) industry in Indonesia has led to the emergence of various lending platforms that provide easy access to financing. However, public trust dynamics, strict regulations, consumerist behaviors, and increasing competition require companies to implement integrated and ethical communication strategies. This study aims to analyze the marketing strategies and public relations (PR) roles in the user acquisition process of the BantuSaku fintech lending platform in Indonesia, as well as to identify the challenges encountered. Employing a qualitative approach with a constructivist paradigm, data were collected through in-depth interviews with BantuSaku internal teams, active users, and industry observers, supported by secondary data including company documents, OJK regulations, and digital content. Analysis was conducted using Miles & Huberman’s (2014) interactive model, covering data reduction, data display, and verification. Findings indicate that marketing strategies emphasizing financial education and transparency, combined with PR efforts focused on building a positive image and managing reputation, significantly contribute to user acquisition and retention. Nevertheless, the effectiveness of these strategies is influenced by low financial literacy, competition with illegal lending services, and default risks. This study highlights the importance of integrating education-based and ethical marketing and PR strategies as a key factor for sustainable growth in fintech lending.